Morphology of poly(vinylidene fluoride) and poly(o-metoxyaniline) blends - Malmonge, L. F. [UNESP]; Mattoso, L. H. C. (Elsevier B.V., 1995)
Blends of poly(o-methoxyaniline) - POMA - and poly(vinylidene fluoride) - PVDF - of various compositions were prepared from organic solvent solutions. Flexible, free-standing and stretchable films were obtained by casting, which were characterized by conductivity measurements, electron microscopy and differential scanning calorimetry. As expected, the blends conductivity increases with increasing contents of the conducting polymer. The onset of the conductivity at low contents of conducting polymer indicates a low percolation threshold for the blends. Despite the presence of the conductive host, the blends displayed the crystalline spherulitic morphology and the beta-phase characteristic of pure PVDF. This morphology appears to be destroyed, however, if the film is stretched by zone-drawing.